Penerapan Pembelajaran Pendidikan Agama Islam Berbasis Higher Order Thinking Skill (HOTS) di SMAN 2 Banjit - Ahmad Fatonik; Latifatus Sadiyah; Erni Styowati; M. Febby Irwansyah; Jaenullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the era of the Industrial Revolution 4.0, Islamic Religious Education (PAI) must emphasize not only memorizing religious content, but also fostering advanced thinking skills such as analysis, evaluation, and creativity through the Higher Order Thinking Skills (HOTS) method. This study aims to describe the implementation of HOTS-oriented Islamic Religious Education (PAI) learning at SMAN 2 Banjit, focusing on implementation methods, supporting and inhibiting factors, and their influence on students. This study uses a qualitative descriptive methodology with data collection methods such as observation, interviews, and documentation. The subjects of the study were Islamic Religious Education (PAI) teachers. Data analysis was carried out by means of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Islamic Religious Education (PAI) teachers at SMAN 2 Banjit have implemented host-based Islamic Religious Education (PAI) teaching methods. HOTS-based learning through discussion methods, advanced question and answer, and problem-based learning, but the implementation has not been evenly distributed across classes. Teachers understand the basic concepts of HOTS, but still face obstacles in preparing HOTS-based learning devices and assessment instruments. Supporting factors for implementation are the support of the principal, technological facilities, and the enthusiasm of some students. Meanwhile, emerging obstacles include a rote-oriented learning culture, unequal distribution of learning facilities, and teacher administrative burdens. The implementation of HOTS has a positive impact on improving students' critical thinking skills and argumentative skills, as well as helping them understand Islamic values ​​more contextually.